Understanding Students’ Perceptions of Arabic Learning Challenges: A Constructivist Study - Sari, Rara Salvia; Yul, Widiya; Andrian, Riko; Ilham (Mantiqu Tayr: Journal of Arabic Language, 2025)
The success of Arabic language education in Islamic higher education largely depends on a deep understanding of the challenges faced by learners. This study critically explores the perceptions of fourth-semester students in the Arabic Language Education program at the State Islamic Institute (IAIN) of Kerinci regarding the difficulties of learning Arabic as a foreign language, using a constructivist approach. Employing a phenomenological method, data were collected through semi-structured interviews and focused group discussions. The findings reveal that students face not only linguistic challenges such as the complexity of Arabic grammar (nahwu) and phonology but also significant affective barriers: learning trauma from past experiences, language anxiety, and a sense of meaninglessness resulting from rote-oriented instruction. A misalignment between instructional approaches and learners’ experiential needs exacerbates these issues. Surprisingly, some students demonstrated resilience and learning creativity through informal study communities and self-directed digital learning. The constructivist perspective highlights how students reconstruct meaning within institutional limitations. This study underscores the urgent need for curriculum reform, teacher training grounded in psychopedagogical awareness, and the empowerment of learner agency. Future research should explore the role of technology and locally contextualized instructional design in promoting more transformative and engaging Arabic language learning experiences.